Effectiveness of exercise training program on postural control and quality of life in middle-aged men with unilateral lower limb amputation - Masoud Kashfi; Iman Khakroo Abkenar; Ali Fakourian; Giovanni Lombardi (Exercise and Quality of Life)
This study aimed to investigate whether the exercise-based amputee rehabilitation program improves postural control and quality of life in people with unilateral transtibial amputation (TTA). Twenty middle-aged men (48.4±3.8 y) with lower limb amputation, in a randomized-controlled longitudinal design, volunteered to participate in the study and were divided into experimental (EXP, n=10) and control (CON, n=10) groups. Before and after 8 weeks of the exercise training program, postural control performance, using one-leg standing (OLS) and Y-balance tests, was measured. The quality of life was also assessed before and after 8 weeks training period using standard questionnaires. Group x time interactions were observed for the EXP group in OLS and Y-balance tests and quality of life scores in comparison to pre- training values and the CON group (p<0.05). People with unilateral TTA who received exercise-based amputee rehabilitation program demonstrated significant improvement in balance performance with significant effects on quality of life.